Alaska Commercial Co's steamship lines to St. Michael and Yukon River [electronic resource] : general offices : 310 Sansome Street, San Francisco. - Alaska Commercial Co. ([San Francisco? : s.n., 1898)
Cover title. Electronic reproduction. Mode of access: Internet. 44